Wireless Lan Security-Role of Smartcards: Integrating Smartcards for Secure Authentication in Wireless LANs (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Wireless LANs based on the IEEE802.11b have emerged as a new standard but still a lot of security issuesremain. One of them issues is the authentication of a terminal to an accesspoint (AP). The IEEE is currently finalizing a framework for security in IEEE802 networks: IEEE 802.1x that is an approved draft, based on the extensibleauthentication protocol (EAP). On another hand, among token technologies,smartcards currently offer the best combination of flexibility, security, andcost among token technologies. They have been chosen by the DoD to be widelydeployed. Therefore it becomes difficult to speak about security withoutevoking smartcards. We have focused our work on the integration of smartcardsfor authentication in wireless networks. In this paper, we will present asmartcard embedding EAP and will show that smartcards could constitute thede-facto device for authentication in Wireless LAN as they have been for GSMand will be for UMTS.